A cross-sectional study on correlates of high blood pressure among school-going children in an Urban Area - Adnatesh V Katta; Prashant R Kokiwar (Wolters Kluwer Medknow Publications, 2018)
Context: School-going children are documenting the increasing incidence of high blood pressure (BP). Compared to adults, the prevalence of hypertension (HT) is low among children, but high BP among them can lead to HT in their adult life. Aim: The aim of was to study the risk factors and correlates of high BP among school-going children. Materials and Methods: A cross-sectional study was carried out for 1½ years among 892 randomly selected school children of 6th-10th class. Measurements such as height, weight, and BP were recorded and classified as per the standard guidelines for given age and sex. Statistical Analysis: Correlation and linear regression analysis were done for continuous variables. For dichotomous variables, mean and standard deviation were calculated and t-test was used in this study. Results: Higher age group, being male, and obesity were found to be significantly associated with elevated systolic BP (SBP) and elevated diastolic BP (DBP). Family history of diabetes and HT was significantly associated with elevated DBP. On linear regression analysis, the studied factors explained 30% variation in SBP and only 12% variation in DBP. Weight and body mass index explained the maximum variation in both SBP and DBP. Conclusion: Overweight or obesity, being male, family history of HT, and increasing age were important risk factors of elevated BP.